Higher Education Institutions’ (HEIS) Awareness towards Blended Learning in Karachi, Pakistan: A qualitative Study - Anum, Ali (2016)
Although Blended Learning has already developed several years and became a successful method to improve the learning system of Higher Education Institutions (HEIs). The evolution of the information technology helps to improve the infrastructure of the HEIs and helps to connect with updated and new technologies around the world. Without any doubt, many educational institutions are adopting and implementing the Information and Communication Technologies (ICT) in their educational structure as they believe that it will add a value in their performance. Many universities are adopting blended learning but still some of the countries do not consider blended learning as an effective tool which means that blended learning has not been accepted fully by the educational institutions around the world. In the context of Pakistan, HEIs are still following the traditional way of the education system and they are not fully aware of the Blended Learning. The research gap between the researcher and the HEIs is really big. In order to explore the level of awareness as well as the perceived challenges of blended learning, the researcher chose to approach the qualitative case study to record different group interviews as an input. Then, recorded interview will help to analysis and process feedback from the participants and get effective output of blended learning. Finally, conclusion and recommendation will be provided after findings of this study. Similarly, the study will also enrich the huge gap of the studies on Awareness of Blended Learning and provide the platform for further studies that will relate when the researchers will examine the Blended learning in Pakistan.